NF-κB decoy oligodeoxynucleotide mitigates wear particle-associated bone loss in the murine continuous infusion model. (1st September 2016) - Lin, Tzu-hua; Pajarinen, Jukka; Sato, Taishi; Loi, Florence; Fan, Changchun; Córdova, Luis A.; Nabeshima, Akira; Gibon, Emmanuel; Zhang, Ruth; Yao, Zhenyu; Goodman, Stuart B.
Graphical abstract: Upper panel, illustration of the murine model with continuous femoral infusion. Mouse distal femurs were exposed to ultra-high molecular weight polyethylene (UHMWPE) particles together with NF-κB decoy oligodeoxynucleotide (ODN) and appropriate controls. Lower panel, trabecular bone structure (blue square) in the distal femur was reconstructed into a 3D image. Yellow lines indicate the major bone loss area induced by UHMWPE particles. Green dotted circle indicated the inserted titanium rod channel from intercondylar region at distal femur. The number of infiltrated macrophages (Mac) and osteoclasts (OC) were determined by immunohistochemistry. UNT: Untreated control. Abstract: Total joint replacement is a cost-effective surgical procedure for patients with end-stage arthritis. Wear particle-induced chronic inflammation is associated with the development of periprosthetic osteolysis. Modulation of NF-κB signaling in macrophages, osteoclasts, and mesenchymal stem cells could potentially mitigate this disease. In the current study, we examined the effects of local delivery of decoy NF-κB oligo-deoxynucleotide (ODN) on wear particle-induced bone loss in a murine continuous femoral particle infusion model. Ultra-high molecular weight polyethylene particles (UHMWPE) with or without lipopolysaccharide (LPS) were infused via osmotic pumps into hollow titanium rods placed in the distal femur of mice for 4 weeks. Particle-induced bone loss was evaluated by μCT, and immunohistochemical analysis of sections from the femur. Particle infusion alone resulted in reduced bone mineral density and trabecular bone volume fraction in the distal femur. The decoy ODN reversed the particle-associated bone volume fraction loss around the implant, irrespective of the presence of LPS. Particle-infusion with LPS increased bone mineral density in the distal femur compared with particle-infusion alone. NF-κB decoy ODN reversed or further increased the bone mineral density in the femur (3–6 mm from the distal end) exposed to particles alone or particles plus LPS. NF-κB decoy ODN also inhibited macrophage infiltration and osteoclast number, but had no significant effects on osteoblast numbers in femurs exposed to wear particles and LPS. Our study suggests that targeting NF-κB activity via local delivery of decoy ODN has great potential to mitigate wear particle-induced osteolysis. Statement of Significance: Total joint replacement is a cost-effective surgical procedure for patients with end-stage arthritis. Chronic inflammation is crucial for the development of wear particle-associated bone loss. Modulation of NF-κB signaling in macrophages (pro-inflammatory cells), osteoclasts (bone-resorbing cells), and osteoblasts (bone-forming cells) could potentially mitigate this disease. Here we demonstrated that local delivery of decoy NF-κB oligo-deoxynucleotide (ODN) mitigated ultra-high molecular weight polyethylene (UHMWPE) wear particle induced bone loss in a clinically relevant murine model. The protective effects of decoy ODN was associated with reduced macrophage infiltration and osteoclast activation, but had no significant effects on osteoblast numbers. Our study suggests that targeting NF-κB activity via local delivery of decoy ODN has great potential to mitigate wear particle-induced bone loss.